DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR THE SIMULTENEOUS ESTIMATION OF OLMESARTAN MEDOXOMIL AND CHLORTHALIDONE IN TABLET DOSAGE FORM - Sawale, Vilas; Dangre, Pankaj; Dhabarde, Disha (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: To develop and validate a simple, rapid, accurate and precise RP-HPLC method for the simultaneous determination of olmesartan medoxomil (OLM) and chlorthalidone (CHL) in pharmaceutical formulation. Methods: Chromatographic separation was performed on a Phenomenox, Gemini C18 (250×4.6 mm, 5 µm) column from thermo isocratic mode with mobile phase 55:45 water: acetonitrile with pH adjusted to 3.0 with ortho phosphoric acid at flow rate 1 ml/min. Peak intensity of both the drugs was monitored at 250 nm with UV detection. Results: The retention time (RT) of OLM and CHL was found to be 2.95 and 3.91 min, respectively. The linearity of OLM and CHL were found in the range of 10-60 µg/ml for OLM and 5-30 µg/ml for CHL. The limit of detection and limit of quantitation was 15ng/ml and 70 ng/ml for OLM and 20 ng/ml and 60 ng/ml for CHL. Conclusion: The proposed method was validated in terms of accuracy, precision, linearity, limit of detection and limit of quantification. Furthermore, no interference was observed with extra pharmacopoeial excipients in tablet suggesting its utility for routine quality control analysis of OLM and CHL in pharmaceutical formulations.